Concentrating on q and cash flow - Grullon, Gustavo; Hund, John; Weston, James P. (Journal of Financial Intermediation, 2018)
Investment spending by US public firms is highly concentrated. The 100 largest spenders account for 60% of total capital expenditures and drive most of the variation in aggregate investment. This high concentration creates a disconnect between the average public firm and macroeconomic aggregates. For large firms, cash flow remains the primary driver of investment spending and has not declined in importance as it has for smaller public firms. The cash flowing to big spenders provides a better forecast of future investment opportunities than noisy proxies for Tobin's q even though these firms are not financially constrained. These results suggest that, at least for the largest spenders, it is unlikely that measurement error drives the significance of cash flow. Our results are also inconsistent with recent models that predict higher investment-cash flow sensitivity for small young growth firms and suggest that cash flow is still the most important determinant of macroeconomic fluctuations in investment spending.